Regional Disparities and Economic Development in Ukraine - Huk, Khrystyna (2022)
In the context of the growing regional disparities in both developed and developing countries, the main aim of this thesis is to investigate the impact of regional disparities on economic development. The research panel used a sample of data in Ukraine for the period from 2004 to 2019. Econometric analysis shows that there is a relationship between variables. Moreover, the impact of individual socio-economic indicators on economic development, in this context, gross regional product, is statistically significant. The indicators considered are regional gross product, regional gross product per capita, population, birth rate, migration, number of higher education students per 10,000 population, agricultural and industrial indices, and regional government expenditures. In conclusion, to reduce regional disparities, it is necessary to increase the share of less developed regions in total funding and production. Adequate coordination of regional development policy at all levels of government should also be helpful in this regard.